Strategi Peningkatan Produktivitas Padi Sawah Di Desa Pelukahan Kecamatan Kuantan Hilir Seberang Kabupaten Kuantan singingi - Ebrila, Rabela; Maharani, Evy; Eliza, Eliza (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Pelukahan Village is one of the villages in Kuantan Hilir Seberang District which has potential in the agricultural sector, especially the commodity rice. The area of paddy fields in Pelukahan Village is 34.9 Ha. The planting index is carried out once a year starting from February to August. Village The crusher has an average productivity of 4 tons. The aim of this research is to formulate strategies and determine priority strategies to increase rice productivity in Pelukahan Village. The data sources used in this research are primary data and secondary data. This research collects data using observation, interviews and documentation studies and reports. Using the SWOT matrix then developed using QSPM. The results of this research show significant differences in strengths, weaknesses, opportunities and threats. The strategy obtained from the SWOT analysis is conducting a comparative study. Providing quality production facilities in farming through coordination with the government and related agencies, providing quality production facilities in farming through coordination with the government and related agencies, seeking the level of technology adoption and post-harvest, coordination with the local government/using superior seed varieties and socialization on time, right form, right target, right use, right dosage, implementing an integrated pest control program, regulating rice planting season patterns based on climate data and appropriate planning, developing partnerships with the private sector for agricultural infrastructure, implementing environmentally friendly pest control technology to overcome pest attacks. The results of the QSPM analysis showed several priority strategies: implementing an integrated pest control (IPM) program , regulate rice planting season patterns based on climate data and appropriate planning, provide quality production facilities in farming through coordination with the government and related agencies, strive for the level of technology adoption in land processing and post-harvest, increase farmer competency by conducting comparative studies.